2020
DOI: 10.1096/fj.201903091rr
|View full text |Cite
|
Sign up to set email alerts
|

Chemically or surgically induced thyroid dysfunction altered gut microbiota in rat models

Abstract: Thyroid hormones are essential for the regulation of energy homeostasis and metabolic processes. However, the relationship between thyroid function and host gut microbial communities is not properly understood. To determine whether and how gut microbiota is associated with thyroid function, metagenomics analysis of the bacterial population in fecal samples of rat models of hyperthyroidism (induced by levothyroxine) and hypothyroidism (induced by propylthiouracil or thyroidectomy) was conducted through 16S rRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
12
1
1
Order By: Relevance
“…Studies in humans showed that hyperthyroid patients had significant enrichments in pathogenic bacteria such as Enterobacteriaceae and Clostridium in the gut in comparison with a healthy group (Zhou et al, 2014), while hypothyroidism was accompanied by a modest intestinal bacterial overgrowth (Lauritano et al, 2007;Zhao et al, 2018). Both rat (Shin et al, 2020) and gerbil models (in the present study) of thyroid dysfunction revealed that profile of gut microbiota varied with different thyroid functional status. We also observed that the hyperthyroid gerbils showed an increase in pathogenic bacteria, such as Rikenella, Helicobacter, Staphylococcus and Veillonella, which have been reported as causes of serious infections and inflammation (Alkadhi et al, 2014).…”
Section: Thyroid Hormones Shaped Metabolic Phenotype and Microbiota Diversitymentioning
confidence: 48%
“…Studies in humans showed that hyperthyroid patients had significant enrichments in pathogenic bacteria such as Enterobacteriaceae and Clostridium in the gut in comparison with a healthy group (Zhou et al, 2014), while hypothyroidism was accompanied by a modest intestinal bacterial overgrowth (Lauritano et al, 2007;Zhao et al, 2018). Both rat (Shin et al, 2020) and gerbil models (in the present study) of thyroid dysfunction revealed that profile of gut microbiota varied with different thyroid functional status. We also observed that the hyperthyroid gerbils showed an increase in pathogenic bacteria, such as Rikenella, Helicobacter, Staphylococcus and Veillonella, which have been reported as causes of serious infections and inflammation (Alkadhi et al, 2014).…”
Section: Thyroid Hormones Shaped Metabolic Phenotype and Microbiota Diversitymentioning
confidence: 48%
“…The effects of MMI/PTU on microbiota were also measured in female adult SD rats (Sun et al, 2020). ATDs increased the alpha-diversity, different from the results in female rats (Shin et al, 2020). The ATD group had more Bacteroidetes, Proteobacteria, and Spirochaetae, but fewer The microbial dysbiosis index (MDI) increased after ATD treatment, indicating that the gut microbiota structure was disturbed in the treatment group.…”
Section: Antithyroid Drugs and Gut Microbiotamentioning
confidence: 73%
“…Methimazole (MMI) and propylthiouracil (PTU) are the commonly used antithyroid drugs (ATDs). ATD can change the gut microbiota structure in wild-type adult rats ( Shin et al., 2020 ; Sun et al., 2020 ) and GD patients ( Sun et al., 2020 ; Chen et al., 2021 ; Huo et al., 2021 ).…”
Section: The Effects On the Gut Microbiota Of Therapeutic Agents For Gd/gomentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, numerous studies have shed light on the crucial role of gut microbiota on multiple metabolic and autoimmune diseases, such as diabetes mellitus, lupus, Alzheimer's disease, obesity, and so on [ 13 , 14 ]. It is well known that the thyroid hormone could influence the gastrointestinal structure and function, especially motility of the gut; meanwhile, a healthy gut microbiota also has beneficial effects on thyroid function [ 15 17 ]. Although there are several studies that explore the relationship between gut microbiota and HT, the composition of gut microbiota in HT with different thyroid function status has been less studied.…”
Section: Introductionmentioning
confidence: 99%